"The water flows under the bridge and we pass above it …" infrastructure, transport and state power: The bridges of Hyderabad city, India c. sixteenth to twentieth centuries. Issue 1 (June 2023) - Cohen, Benjamin B.
In the late sixteenth century and again in the nineteenth and early twentieth centuries the rulers of Golconda and Hyderabad (India) faced a problem of urban congestion around the Musi River. The river impeded movement between growing urban areas on either bank and during the monsoon it flooded making transport nearly impossible. To resolve this issue, they constructed four bridges across the Musi, often with assistance from local British officials. These bridges served as critical infrastructure technology for urban transport and mobility. Forms of state power, from a sultan to an indigenous prince to colonial officials, all worked to finance, design, and build these bridges thus allowing urban Hyderabad to both encompass and grow beyond the challenges of the river.